The Vision of God in Transcendental Philosophy - Sayyid Muhammad tabatabai (حکمت اسرا, 2010)
One of the issues discussed in theology is the ‘beatific vision,’ or seeing God. The Mushibbahah and Mujassimah sects, taking their lead from some Jewish groups, hold that God has a body and hence He can be seen. The AshÝarÐ sect, while they do not believe God to have a material body, surmise that He is visible to the believers during the Resurrection and have gone one to support their claim by putting forward rational and traditional proofs. The MuÝtazili and the Imamiyyah however see the claim of the AshÝarÐ’s to be in conflict with their bases and premises. Imam KhumaynÐ (r) holds that the beatific vision is a possibility, but with the heart and based upon the reality of faith. He was of the belief that true faith in the station of divine unicity (tawÎÐd) and sanctity (or grace, walÁyah) removes the veil impeding the vision, and went on to stress that any knowledge that is not tantamount to faith in and fear of God is the greatest of veils. In line with this, the Imam saw faith to be a divine light that makes the heart to be the locus of divine manifestations and effusions. He also held that there was a link between faith, the practice of good deeds, and the meeting with God, such that if a man were to have faith and do good deeds, he would, by the grace of God and in accordance with his level of faith and measure of deeds, be able to work wonders.